Dynamic Capabilities, Resources, and Social Capital in Creating Sustainable Competitive Strategies in Indonesian MSME - Susiang, Maria Imelda Novita (IJBLE Scientific Publications Community Inc., 2024)
The purpose of this study is to better understand how Indonesian Micro, Small, and Medium-Sized Enterprises (MSMEs) shape sustainable competitive strategies through the interaction of dynamic capabilities, resources, and social capital. The study employed a quantitative methodology that utilized Structural Equation Modeling with Partial Least Squares (SEM-PLS 3) to extract data from a representative sample of 232 MSMEs located in different industries and geographies. The results show that social capital, resources, dynamic capacities, and sustainable competitive strategies are all positively correlated. The study also reveals the mediating functions of social capital and resources in converting dynamic capabilities into long-term competitive advantages. With a robust R-squared value and a Goodness of Fit (GoF) rating of 0.68, the model demonstrates a substantial fit, indicating its adequacy in explaining the intricacies of the MSME environment in Indonesia. These revelations have important ramifications for developing theories as well as useful tactics to raise MSMEs' competitiveness in Indonesia.